Meta-Analysis of the Validity and Practicality of Problem-Based Learning-Oriented Student Worksheets Integrated with Islamic Values for Phase E Students at Madrasah Aliyah (MA) - Azhari, Azhani; Zulyusri, Zulyusri (Lembaga Yasin AlSys, 2025)
Education is crucial for developing human resources (HR) capable of meeting the challenges of the modern era. As an Islamic educational institution, Madrasah plays a vital role in cultivating human resources with strong character and competitiveness. This study investigates the feasibility of Problem-Based Learning (PBL)-oriented Student Worksheets (LKPD) integrated with Islamic values within Madrasah Aliyah (MA) to enhance student learning outcomes. Employing a meta-analysis methodology, we synthesized data from 10 scholarly articles, utilizing tabulation techniques to assess the validity and practicality of the LKPD. The findings revealed an average validity level of 89.97%, categorizing it as highly valid, and an average practicality score of 88.72%, indicating high practicality. This analysis demonstrates that PBL-oriented LKPD integrated with Islamic values significantly enhances student engagement, creativity, and problem-solving skills while fostering the internalization of Islamic values among students in Phase E at Madrasah Aliyah. Consequently, the implementation of such learning materials not only improves academic understanding but also enriches the educational experience by integrating subject matter, Islamic values, and problem-solving within the learning process, highlighting their broader scholarly relevance and potential real-world impact.